2021
DOI: 10.1051/0004-6361/202039780
|View full text |Cite
|
Sign up to set email alerts
|

Mixed properties of magnetohydrodynamic waves undergoing resonant absorption in the cusp continuum

Abstract: Context. Observations of magnetohydrodynamic (MHD) waves in the structured solar atmosphere have shown that these waves are damped and can thus contribute to atmospheric heating. In this paper, we focus on the damping mechanism of resonant absorption in the cusp continuum. This process takes places when waves travel through an inhomogeneous plasma. Aims. Our aim is to determine the properties of MHD waves undergoing resonant absorption in the cusp continuum in the transition layer of a cylindrical solar atmosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Our continuum eigenfunctions match the resistive eigenfunctions of Fig 1 . in Goossens et al (2021) quite well, except for ξ r . In Fig.…”
Section: Kink Modesmentioning
confidence: 82%
See 1 more Smart Citation
“…Our continuum eigenfunctions match the resistive eigenfunctions of Fig 1 . in Goossens et al (2021) quite well, except for ξ r . In Fig.…”
Section: Kink Modesmentioning
confidence: 82%
“…The eigenfunctions P 1 , ξ r , ξ ϕ and ξ z of the continuum mode obtained from our series method in ideal MHD and corresponding to the resistive kink eigenmode shown by Goossens et al (2021) in their Fig. 1 and Fig.…”
Section: Kink Modesmentioning
confidence: 99%
“…it is compressible as a magnetoacoustic wave but has also non-zero parallel vorticity as an Alfvén waves. This is explained in, e.g., Goossens et al (2021). When the discontinous variation of density is replaced by a continuous variation in a transitional layer Goossens et al (2012) found that the fundamental radial mode of kink waves is resonantly damped but has both non-zero Eulerian perturbation of total pressure everywhere and nonzero parallel vorticity in the non-uniform transitional layer.…”
Section: Various Mhd Modes and Kink Waves In Structured Non-uniform F...mentioning
confidence: 97%
“…This would result in the possibility of resonance occuring between the main oscillation of the structure and local slow mode oscillations in the boundary layer, as studied theoretically by Yu et al (2017). The analytical derivations of Goossens et al (2021) show that, when slow waves are resonantly absorbed in the cusp continuum, both the azimuthal component of vorticity and the parallel component of the plasma displacement are large. The huge amount of vorticity could indicate the possibility of the KHI developing in those conditions.…”
Section: Modelmentioning
confidence: 98%
“…(30) therein). Assuming a sinusoidal transition profile with width l = 0.1R (where R is the radius of the pore) in the squared cusp and sound speeds, a ratio of external to internal magnetic field of B 0ze /B 0zi = 0.33, a cusp resonant position at r C = 0.955R (based on the numerical computations of Goossens et al (2021)), a value for the perturbed total pressure at the resonant position equal to its value on the interface for the corresponding surface mode in the absence of the transition layer, a real part of the frequency equal to the frequency of the corresponding surface mode in the absence of the transition layer, and a magnetic Reynolds number of 10 7 to have a lowerbound on resistivity and thus an upperbound on realistic values for the longitudinal velocity at the resonance, we found a value of M A = 0.36 around the cusp resonance point for a sausage mode with k z R = 2. This value of k z R is within the range of validity for the longitudinal wavenumber of the observed slow surface sausage mode in a photospheric pore by Grant et al (2015).…”
Section: Photospheric Poresmentioning
confidence: 99%